The Internal Market Community Law as source of Administrative National Powers Legitimate Action - Sobreira, Carlos Pedro (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2005)
The present study seeks to highlight the impact of European internal market rules. on the functioning of national administrative powers. At the same time we seek to understand the jurisprudential reasoning of the European Court of Justice as it claims that national executive powers must act accordingly to internal market rules. Thus the principles of direct effect and supremacy turned out as new sources of national executive's powers legitimate action. In view of that the traditional concept of public national good is at stake.